Cerebellar transcranial magnetic stimulation to treat drug‐resistant epilepsy: A randomized, controlled, crossover clinical trial - Wang, Yuan‐Yuan; Ma, Lei; Shi, Xiao‐Jing; Liu, Yu; Wu, Dian‐Wei; Hao, Jian‐Min; Leng, Xiu‐Xiu; Jin, Lang; Yuan, Fang; Sun, Zhong‐Qing; Zhao, Jing‐Jing; Wang, Ling; et al. (Epilepsia (Copenhagen), 2025)
Objective Epilepsy is one of the most prevalent brain diseases. Approximately one third of patients consistently experience drug‐resistant epilepsy (DRE), a condition where seizures persist despite the use of antiseizure medications. Exploration of new therapies for DRE is urgently needed. In this single‐center, randomized, sham‐controlled, crossover clinical trial (NCT05042726), we aimed to investigate the effectiveness and safety of transcranial magnetic continuous theta burst stimulation (cTBS) targeting the cerebellum to treat DRE. Methods Patients with DRE for ≥2 years and a seizure frequency of ≥2 seizures per month were enrolled and randomized 1:1 to receive active stimulation followed by sham stimulation or vice versa. The bilateral cerebellum was targeted by navigated cTBS focusing on the cerebellar dentate nucleus, once daily on workdays for 2 weeks. The primary outcomes were the percentage of seizure reduction and 50% responder rate in the per‐protocol population within 2 months after treatment. Results Forty‐four patients were enrolled and randomized; 18 patients in the active stimulation‐first group and 20 in the sham stimulation‐first group were included in the final analysis. Active cTBS significantly reduced seizures compared to sham stimulation (difference in percentage of seizure reduction between treatments = 25%, 95% confidence interval [CI] = 5%–46%, p = .018). The 50% responder rate after active stimulation was significantly higher than that after sham stimulation (difference in 50% responder rate between treatments = 24%, 95% CI = 11%–40%, p = .029). Adverse events occasionally occurred during active stimulation (moderate headache in 5% of patients, tinnitus in 3% of patients, dizziness in 3% of patients) but resolved spontaneously within days after treatment completion. Significance This trial suggested that cTBS targeting the cerebellum was effective and well tolerated in the treatment of DRE. Further studies are warranted to confirm its effectiveness and mechanism.